Students' survey for assessing HE teachers' work - advantages and disadvantages - Violeta Janusheva; Milena Pejchinovska; Jove D. Talevski (Universidade Federal de Santa Maria, 2018)
A self-evaluation survey is one of the basic tools used by every higher education institution for the purpose of identifying and improving the quality of its educational services. A relevant segment of the self-evaluation procedure is the work of the HE teacher; the assessment is provided via a survey filled in by each course student's attendants respectively. Therefore, the aim of this paper is to show the advantages and disadvantages of the students' survey as a part of the self-evaluation process at the "Sv. Kliment Ohridski" University in Bitola, Republic of Macedonia. The research has a qualitative paradigm, i.e. the twelve survey statements within this survey are analyzed regarding the impact they have on the validity and objectivity of the results to be provided about the HE teachers' work quality, and regarding their relevance in the multidimensional teaching construct. The research has also a quantitative paradigm, i.e. an analysis of the opinions of 100 HE teachers of this University about the effects of the students' survey answers on their teaching, and an analysis of 200 students of this University about the efficiency of the survey they fill in. The research has a descriptive design. The methods used for processing the data and for gaining conclusions consist of analyses, syntheses and comparison. The research results indicate that besides the advantages, this students' survey has numerous disadvantages that should be taken into account because they influence both the validity and the objectivity of the grade given to the HE teachers' work. It consequently imposes the need for urgent revision of the survey questions.